Applying feminist legal principles to achieve gender equality in Vietnam’s labor legislation - Minh Hoang Dang (Cogent Social Sciences, 2024)
This article examines the application of feminist legal theory to Vietnam’s labor laws for advancing gender equality. Utilizing normative legal research methods, the study critically analyzes these laws, highlighting the integration of gender equality principles and their limitations. The analysis reveals deep-seated gender biases, indicating that Vietnamese female workers’ realities are inadequately reflected in the legal provisions. Feminist legal theory is employed to critique the reinforcement of women’s subordination by the legal system, urging reforms that recognize women’s experiences to eradicate gender biases. The study champions a feminist legal approach to reassess ‘neutral’ legal clauses and counteract biased interpretations, pivotal for exposing and rectifying the laws’ subtle perpetuation of gender inequalities. It advocates for a shift in labor law to a more inclusive framework that champions gender equity, abolishes discriminatory practices, and empowers women. This approach emphasizes the necessity of embedding gender perspectives in legal analysis and reform, aiming to create a fairer legal framework in Vietnam that aligns with international standards and authentically represents gender diversity in the labor market. The proposed paradigm shift seeks not only to meet global benchmarks but to genuinely embody inclusivity and fairness, transforming the labor landscape for all workers, particularly women and marginalized groups.